Faktor-Faktor Peran Dan Struktur Audit Determinan Kinerja Auditor - Muhsin, Muhsin (Fakultas Ekonomi Universitas Gresik, 2023)
Auditor performance is a reflection of the work done to achieve better or more prominent results in achieving organizational goals Fanani et al, 2008. Among the indices used for the determination good or bad work results is auditor performance which is the work that carried out by the auditor in accordance with the responsibilities given to him. When evaluating audit results, clients and the general public pay great attention to the auditor's performance. RSM Salustro Reydel in France once made a mistake when auditing Vivendi Universal. While the performance of the auditor is an evaluation of the work performed by employees, both from superiors to direct subordinates and colleagues. Inequality between this discussion and the previous discussion lies in the research setting, namely the first sample of this research is students who have passed auditing 2, where they are able to understand the audit structure, role conflicts and the ambiguity of the role and performance of the auditor, because most of them act as students who will always want to achieve auditor performance. the best. To examine the behavior of each individual student who is still young so that there are not many role conflicts and role ambiguity. This study uses a quantitative method, namely the method used in completing a scientific research with the aim of solving the problem being studied, namely the determinants of auditor performance. Descriptive statistical analysis is useful for conveying the results of a quantitative analysis. Â«Conflict is a process where a person believes that another person has had a bad impact or will have a bad impact on himÂ». So that the auditor experiences role conflict, which is a state of mind caused by two sets of competing demands which can lead to reduced motivation at work, which in turn can reduce overall performance. In line with the stewardship theory that auditors prioritize office goals rather than individual goals, so they can maintain better audit performance